Alih Fungsi Lahan dan Dampaknya pada Perubahan Kehidupan Masyarakat Sekitar (Studi Kasus: Alih Fungsi Lahan pada PT Hardases Abadi Indonesia (HAI) di Desa Wangandowo, Kecamatan Bojong, Kabupaten Pelalongan) - Nurmulia, Rahmi; Furqon, Imahda Khoiri (Glossary : Jurnal Ekonomi Syariah, 2025)
This research discusses the land conversion carried out by PT Hardases Abadi Indonesia (HAI) in Wangandowo Village, Bojong District, Pekalongan Regency, and its impact on the lives of the surrounding community. Land that was originally in the form of hills and forests was converted into an industrial area for the construction of a shoe factory with a building area of 184,638 square meters. This land conversion has a positive economic impact in the form of local labor absorption and increased community welfare. However, the land use change also caused serious environmental impacts, such as the loss of water catchment areas and the occurrence of flash floods due to the collapse of the factory's embung in March 2024 which damaged residential areas and caused casualties. The research used a qualitative approach with interviews, observation and documentation to explore the socio-economic and environmental impacts. The results emphasized the need for strict environmental management and sustainable spatial planning so that industrial development can run in balance with environmental sustainability and community welfare.